2013
DOI: 10.1177/1357633x12474963
|View full text |Cite
|
Sign up to set email alerts
|

An international pilot study of asynchronous teleconsultation for oropharyngeal dysphagia

Abstract: We investigated whether an expert's consultation provided via telemedicine could improve the quality of care for patients with dysphagia. A trained clinician completed videofluoroscopic swallowing studies (VFSS) of 17 consecutive patients in a Greek hospital. The videofluoroscopic images were then stored on a website for independent review by an expert Speech and Language Pathologist in the US. An extra Rater evaluated 20% of all data for additional reliability testing. Eight diagnostic indicators of swallowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 10 publications
1
46
0
3
Order By: Relevance
“…Specifically, over the last decade, there have been several research studies examining the effectiveness and clinical utility of telehealth services in dysphagia management (Malandraki, McCullough, He, McWeeny, & Perlman, 2011;Malandraki et al, 2013;Malandraki, Roth, & Sheppard, 2014;Sharma, Ward, Burns, Theodoros, & Russell, 2011;Ward, Burns, Theodoros, & Russell, 2013;Ward, Sharma, Burns, Theodoros, & Russell, 2012a, 2012bWard et al, 2007). Most of these studies have primarily focused on adult patients and have demonstrated positive results on the feasibility and reliability of remote dysphagia evaluations (Malandraki et al, 2011;Malandraki et al, 2013;Sharma et al, 2011;Sharma, Ward, Burns, Theodoros, & Russell, 2012;Ward et al, 2013;Ward, Sharma, Burns, Theodoros, & Russell, 2012a;Ward, E. C., Sharma, S., Burns, C., Theodoros, D., & Russell, 2012b;Ward et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, over the last decade, there have been several research studies examining the effectiveness and clinical utility of telehealth services in dysphagia management (Malandraki, McCullough, He, McWeeny, & Perlman, 2011;Malandraki et al, 2013;Malandraki, Roth, & Sheppard, 2014;Sharma, Ward, Burns, Theodoros, & Russell, 2011;Ward, Burns, Theodoros, & Russell, 2013;Ward, Sharma, Burns, Theodoros, & Russell, 2012a, 2012bWard et al, 2007). Most of these studies have primarily focused on adult patients and have demonstrated positive results on the feasibility and reliability of remote dysphagia evaluations (Malandraki et al, 2011;Malandraki et al, 2013;Sharma et al, 2011;Sharma, Ward, Burns, Theodoros, & Russell, 2012;Ward et al, 2013;Ward, Sharma, Burns, Theodoros, & Russell, 2012a;Ward, E. C., Sharma, S., Burns, C., Theodoros, D., & Russell, 2012b;Ward et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the management of dysphagia, telehealth has also been shown to significantly improve health outcomes and quality of care (Malandraki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The virtual attendance is already discussed in science and also explored by Speech Language Pathology 8,9,11,12,16 . Internet, digital world, and communication networks are already tele-health services and found in worldwide [9][10][11][12]16,17 and Brazilian 8,18-20 clinician practice.…”
Section: Resultsmentioning
confidence: 99%
“…Internet, digital world, and communication networks are already tele-health services and found in worldwide [9][10][11][12]16,17 and Brazilian 8,18-20 clinician practice. Since this is a new subject in Brazil there were not found many researches about tele-health in speech language pathology.…”
Section: Resultsmentioning
confidence: 99%
“…As skills in VFSS are considered to be advanced skills (227,228), this model could be useful in upskilling local therapists. Few studies have been published in this area (229)(230)(231), although a paper in 2016 found that adult swallowing could be reliably assessed via telepractice. Future studies into paediatric VFSS via telepractice are warranted to further develop the potential of this model.…”
Section: Suitability Of Patient Groups and Services For Telepractice mentioning
confidence: 99%